Identification and Validation of a Prognostic 5-Protein Signature for Biochemical Recurrence Following Radical Prostatectomy for Prostate Cancer - Lv, Daojun; Cao, Zanfeng; Li, Wenjie; Zheng, Haige; Wu, Xiangkun; Liu, Yongda; Gu, Di; Zeng, Guohua (Frontiers in Surgery, 2021)
Abstract Background: Biochemical recurrence (BCR) is an indicator of prostate cancer (PCa)-specific recurrence and mortality. However, there is a lack of an effective prediction model that can be used to predict prognosis and to determine the optimal method of treatment for patients with BCR. Hence, the aim of this study was to construct a protein-based nomogram that could predict BCR in PCa. Methods: Protein expression data of PCa patients was obtained from The Cancer Proteome Atlas (TCPA) database. Clinical data on the patients was downloaded from The Cancer Genome Atlas (TCGA) database. Lasso Cox regression was conducted to select the most significant prognostic proteins and formulate a protein signature that could predict BCR. Subsequently, Kaplan-Meier survival analysis, univariate and multivariate Cox analyses were conducted to evaluate the performance of the prognostic protein-based signature. Additionally, a nomogram was constructed using multivariate Cox proportional hazards regression. Results: We constructed a 5‐protein-based prognostic prediction signature that could be used to identify high‐risk and low‐risk groups of PCa patients. The survival analysis demonstrated that patients with a higher BCR showed significantly worse survival than those with a lower BCR (p < 0.0001). The time-dependent receiver operating characteristic curve showed that the signature had an excellent prognostic efficiency for 1‐year, 3‐year and 5‐year BCR (area under curve in training set: 0.691, 0.797, 0.808 and 0.74, 0.739, 0.82 in the test set). Univariate and multivariate analyses indicated that this 5‐protein signature could be used as independent prognosis marker for PCa patients. Moreover, nomogram and calibration plots confirmed the predictive value of this 5‐protein signature in 3-year, 5-year and 10-year BCR overall survival (C-index: 0.764, 95% confidence interval: 0.701 to 0.827). Conclusions: Our study identified a 5-protein-based signature and constructed a prognostic nomogram that could reliably predict BCR. The findings might be of paramount importance for the prediction of PCa prognosis and medical decision-making.